To train academics in the use of formative, constructive, transformative assessment of learning - Raffaela Tore; Diletta Peretti (Firenze University Press, 2020)
In an employability perspective and to ensure inclusive and quality training, at international level, the professors of the University are working hard through their training to improve the teaching methodologies used in their courses (EUA, 2019; Unesco, 2015). To achieve this objective can contribute the use of evaluation in a formative, constructive and transformative of learning. In this context, the article reports on a training activity experienced by the teaching staff of the University of Cagliari, referring to the module on evaluation during the project Discentia.   Formare gli accademici all'uso della valutazione formativa, costruttiva, trasformativa dell'apprendimento In un'ottica di employability e al fine di garantire una formazione inclusiva e di qualità, a livello internazionale i docenti universitari si stanno impegnando attraverso la propria formazione per migliorare le metodologie didattiche usate nei loro corsi (EUA, 2019; Unesco 2015). A raggiungere questo obiettivo può contribuire l'uso della valutazione in funzione formativa, costruttiva e trasformativa dell'apprendimento. Facendo riferimento a questo contesto l'articolo riporta un'attività di formazione esperita dal personale docente dell'Università di Cagliari riferita al modulo sulla valutazione nell'ambito del progetto Discentia.